PREVALENCE OF NASOPHARYNGEAL CARCINOMA PATIENTS IN DEPARTEMENT OF ORL-HNS HASAN SADIKIN GENERAL HOSPITAL 2010 -2017 - Riri Handayani; Yussy Afriani Dewi; Deasy Z Madani (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: Nasopharingeal Carcinoma starting from Rosenmuller fossa and intracranial or local spread as a mass in the head area. Nasopharyngeal carcinoma is also associated with hearing problems, serous otitis media, tinnitus, nasal congestion, anosmia, nose bleeding, difficulty swallowing, and dysphonia. Nasopharyngeal carcinoma is a disease that spreads globally and divides races around the world. The purpose of this study is to determine the prevalence of nasopharyngeal disease in Otorhinolaringology-Head and Neck Department, Dr. Hasan Sadikin General Hospital Bandung in 2010-2017. Methods: Medical record method description of Nasopharyngeal Carcinoma at Departement of Otorhinolaringology- Head and Neck Surgery, Dr. Hasan Sadikin General Hospital Bandung in 2010-2017 that used sampling method. Results: There were 1378 patients nasopharyngeal carcinoma, 976 people that included, 657 were men and 319 were women. Obtain most elementary school education (54.9 %) the majority of male patients (67.3 %) with various job background, whereas female patients were housewives (28.1%), and those aged 41-50 years (34%). Most histopathology are undifferentiated carcinoma (58.3 %). Conclusion: Nasopharyngeal Carcinoma patients at the Otorhinolaringology-Head and Neck Surgery Departement. Dr. Hasan Sadikin General Hospital Bandung are 1378 cases. There was higher instance in middle age, and older men and elementary school educated with major histopathology finding was undifferentiated carcinoma